2017 IEEE Wireless Communications and Networking Conference Workshops (WCNCW) 2017
DOI: 10.1109/wcncw.2017.7919039
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Polar Code Construction for Higher-Order Modulation

Abstract: Abstract-An efficient algorithm for the construction of polar codes for higher-order modulation is presented based on information-theoretic principles. The bit reliabilities after successive demapping are estimated using the LM-rate, an achievable rate for mismatched decoding. The successive demapper bit channels are then replaced by binary input Additive White Gaussian Noise (biAWGN) surrogate channels and polar codes are constructed using the Gaussian approximation (GA). This LM-rate Demapper GA (LM-DGA) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…The results show a slight gain in performance with respect to the state of the art transmission scheme proposed in [1]. Additionally, we demonstrated that the existing approaches of designing polar codes for the AWGN channel via biAWGN channel surrogates [6] can be extended to design polar codes on the PPM Poisson channel. We observed that the list size of the dynamic successive cancellation list decoder has an impact on the performance of the scheme.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The results show a slight gain in performance with respect to the state of the art transmission scheme proposed in [1]. Additionally, we demonstrated that the existing approaches of designing polar codes for the AWGN channel via biAWGN channel surrogates [6] can be extended to design polar codes on the PPM Poisson channel. We observed that the list size of the dynamic successive cancellation list decoder has an impact on the performance of the scheme.…”
Section: Discussionmentioning
confidence: 83%
“…To refer to a label at a generic time instance we drop the subscript i and write b = b 1 · · · b m [6]. The input x i to the PPM Poisson channel is the output of the PPM mapper defined as…”
Section: E Ppm Mapping and Demappingmentioning
confidence: 99%
See 1 more Smart Citation
“…3 shows the performance of 64-QAM polar and BMERA codes with n = 256 QAM symbols per block and a spectral efficiency of 3 bits per channel use over the AWGN channel. All codes are optimized for a SNR of E s /N 0 = 11 dB using the methods of [11] with set partitioning label. The comparison shows a similar result as in the BPSK case.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Polar-coded modulation (PCM) is discussed in [5]- [7]. The performance comparison and efficient code design methods of three polar-coded modulation schemes are presented in [8,Fig. 11].…”
Section: Introductionmentioning
confidence: 99%